2015
DOI: 10.1021/acsami.5b06170
|View full text |Cite|
|
Sign up to set email alerts
|

Ni Mg Mixed Metal Oxides for p-Type Dye-Sensitized Solar Cells

Abstract: . (2015) Ni Mg mixed metal oxides for p-type dye-sensitized solar cells. ACS Applied Materials and Interfaces, 7 (44). pp. 24556-24565. ISSN 1944-8252 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/34661/1/Mg_NiO_resubmitted.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Creative Commons Attribution Non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The device based on hierarchical NiO/CMK-3 shows a higher J sc (5.25 mA cm -2 ) than that based on NiO clusters (2.86 mA cm -2 ). The higher J sc of the NiO/CMK-3 can be explained by the high specific surface area of the nanocomposite (508 m 2 g -1 ), which is far higher than that previously reported [9,19,20,[35][36][37]. CMK-3 has a high specific surface of 1091 m 2 g -1 , and in the hierarchical structure acts as a template that effectively prevents the self-aggregation of NiO.…”
Section: Discussionmentioning
confidence: 68%
“…The device based on hierarchical NiO/CMK-3 shows a higher J sc (5.25 mA cm -2 ) than that based on NiO clusters (2.86 mA cm -2 ). The higher J sc of the NiO/CMK-3 can be explained by the high specific surface area of the nanocomposite (508 m 2 g -1 ), which is far higher than that previously reported [9,19,20,[35][36][37]. CMK-3 has a high specific surface of 1091 m 2 g -1 , and in the hierarchical structure acts as a template that effectively prevents the self-aggregation of NiO.…”
Section: Discussionmentioning
confidence: 68%
“…The shifting of Fermi energy due to the carrier concentration thereby explain the drop in flat‐band potential for sample with Al content >25 mol%. The increase in CBM energy might affect the electron injection rate from the excited dye to the photoanode . The results showed that the V OC of the DSSCs is directly affected by the flat‐band potential, indicating that the drag of injection rate is negligible with CBM playing the most crucial part in V OC determination.…”
Section: Resultsmentioning
confidence: 98%
“…Photoelectron spectra contain a wealth of qualitative and quantitative information, but in some circumstances, can be extremely complex with the spectra of lanthanides prime examples 58 . Such complexity poses real challenges to even the most experienced analysts and one must always be on guard against commonly encountered errors such as incorrectly attributing peak asymmetry, satellite structure, multiplet splitting or screened photoemission peaks to non-stoichiometric or high oxidation states (see for example [59][60][61][62][63][64][65][66] ). An excellent paper on the use and misuse of curve fitting is given by Sherwood 67 , and we highlight some of the points raised in that paper in the following sections.…”
Section: Spectral Interpretationmentioning
confidence: 99%